An overview of oral pediatric infectious diseases - Aljohani, Hanan Raja; Almansour, Sara Hamed; Mobarki, Areej Solaiman; Jaafari, Wejdan Aqeel; Al-mohaya, Deema Abdullah; Ali, Mohammed Wazir; Aldaini, Bedour Omar; Nogali, Nermin Ahmed; Almimony, Hatem Abduljabar; Hafez, Majed Hussain; Almazariqah, Shaeea Ali (International Journal Of Community Medicine And Public Health, 2024)
Pediatric oral infectious diseases, caused by a range of viral, bacterial, and fungal pathogens, represent a significant challenge in clinical practice. These infections, often influenced by age, immune status, and hygiene practices, can lead to pain, functional impairments, and systemic complications. Common viral infections such as herpetic gingivostomatitis, varicella-zoster virus (VZV) manifestations, and hand-foot-and-mouth disease present with characteristic oral lesions, often accompanied by systemic symptoms. Bacterial infections, including dental caries, gingivitis, and odontogenic infections, are primarily linked to microbial colonization, dietary habits, and poor oral hygiene. Advanced cases, such as necrotizing periodontal diseases, can have severe implications if not managed promptly. Fungal infections, predominantly caused by Candida species, occur frequently in neonates and immunocompromised children, manifesting as oral thrush or angular cheilitis, and require targeted antifungal therapy. Prevention strategies, including the use of fluoride, dietary counseling, and regular dental check-ups, play a pivotal role in reducing the incidence of these infections. Management approaches vary based on the pathogen and clinical severity, ranging from supportive care and antifungal agents to antibiotic therapy and surgical interventions in severe cases. Collaborative care between dental practitioners and other healthcare providers is essential for effective outcomes. Infection control measures within dental settings and public health initiatives, such as vaccination and oral health education, are crucial in minimizing transmission and recurrence. Addressing pediatric oral infectious diseases requires a multifaceted approach, incorporating individualized patient care, preventive measures, and public health strategies to promote optimal oral and systemic health outcomes. Continued research and innovation are vital to improving diagnostic tools and therapeutic options for managing these infections in pediatric populations.